Targets for chimeric antigen receptor T-cell therapy of acute myeloid leukemia - Schorr, Christopher; Perna, Fabiana (Frontiers in Immunology, 2022)
Acute Myeloid Leukemia (AML) is an aggressive myeloid malignancy associated to high mortality rates (less than 30% 5-year survival). Despite advances in our understanding of the molecular mechanisms underpinning leukemogenesis, standard-of-care therapeutic approaches have not changed over the past decades. Chimeric Antigen Receptor (CAR) T-cell therapy targeting CD19 has shown remarkable clinical outcomes for patients with acute lymphoblastic leukemia (ALL) and is now an FDA-approved therapy. Targeting of myeloid malignancies that are CD19-negative with this promising technology remains challenging largely due to lack of alternate target antigens, complex clonal heterogeneity, and the increased recognition of an immunosuppressive bone marrow. We carefully reviewed a comprehensive list of AML targets currently being used in both proof-of-concept pre-clinical and experimental clinical settings. We analyzed the expression profile of these molecules in leukemic as well normal tissues using reliable protein databases and data reported in the literature and we provide an updated overview of the current clinical trials with CAR T-cells in AML. Our study represents a state-of-art review of the field and serves as a potential guide for selecting known AML-associated targets for adoptive cellular therapies.